The Role Of Valwes In Forming The Identity of Migrants - Kamila, Aliyeva (2021)
On the leading role of values for the development of identity and ensuring the effective adaptation of migrants to the new ethnocultural environment, during the research process, we set the task to identify the values of migrants living in Azerbaijan. At the same time, such factors as the length of residence in the country and the age of the respondents were taken into account. The study involved 235 migrants, of whom 98 are Koreans and 137 Turks, who have been living in Azerbaijan for at least five years, aged 18-40. There are 55 women among Koreans, 43 men, 87 men and 50 women among Turks. The results of our study showed that the lower the level of national identity, the greater the opportunity for migrants to choose a marginal adaptation strategy. This behavior strategy leads to dissatisfaction, social and psychological safety of the migrant. Having lost the values of their culture, the migrant loses an adequate standard “image of the world”, which underlies the adaptation of the individual to the social environment. This means that the individual lacks values, patterns of adequate behavior, he has lost the significance of his culture, and therefore cannot adequately assess and accept the values of the host culture. Research has shown that a high level of indicators on such scales as the scale of interactivity (19%) and the scale of adaptation (18%) indicates that respondents feel confident enough in the new environment, are open to cooperation and are focused on self-realization, which gives them a sense of social and physical security. This situation, naturally, lowers the indicator on the scale of depression, which indicates the absence of serious emotional problems.